MENINGKATKAN KEMAMPUAN INOVASI MELALUI ORIENTASI KOMPETITOR PROAKTIF DAN RESPONSIF: PERSPEKTIF TEORI KAPABILITAS DINAMIS - Rosmita; Septian Wahyudi (stiatabalong.ac.id, 2025)
BUMDesa has an important role as a driver of the village economy and community empowerment by utilizing local potential and wisdom. However, many BUMDesa still face challenges in adapting to market dynamics and creating relevant innovations. This study aims to examine the effect of proactive and responsive competitor orientations on the innovation capabilities of BUMDesa in Riau Province. Data were collected from 192 advanced BUMDesa through questionnaires distributed directly. Data analysis was conducted using SPSS to test the relationship between competitor orientation and innovation capabilities. The results show that proactive competitor orientation plays a major role in helping BUMDesa detect market opportunities early, while responsive competitor orientation supports the ability to adapt to market changes. Together, both have been shown to increase BUMDesa's innovation capabilities. This study provides practical benefits by encouraging BUMDesa managers to implement more adaptive strategies, utilize technology, and expand cooperation networks. From a policy perspective, these results serve as a basis for local governments to develop relevant training and support programs. Theoretically, this research also enriches the development of Dynamic Capability Theory in the context of community-based organizations, although it is still limited to the scope of the Riau Province area and a quantitative approach, so that it can be a reference for further research. Keywords: Dynamic capability theory, proactive competitor orientation, responsive competitor orientation, Innovative Capability